Stress Patterns and Failure Around Rough Interlocked Fault Surface. Issue 7 (29th July 2019) - Sagy, Amir; Lyakhovsky, Vladimir
Abstract: Fault zones accumulate stress during interseismic periods and release it by slip along fault surfaces. We explore the effect of fault roughness on stress patterns and failure conditions around interlocked fault surfaces using an analytical approach. Measured slip surface geometry of different fault outcrops parallel to the slip demonstrates surface roughness at outcrop scales generally confined between 0.001 L 0.5 and 0.01 L 0.8, where L is the section length. These two power law end‐members are utilized for exploring the influence of scale‐dependent geometrical undulations on stress and failure conditions. Off‐fault static stress pattern is calculated based on perturbation theory. Stress amplification and failure conditions around the surfaces are controlled by the ratio between roughness amplitude to wavelength, and therefore, small power values increase failure associated with short roughness wavelengths, immediately nearby the interface. Increasing both amplitude to wavelength ratio and amplitude heights enhance failure in zones around the interface, but at the same time decreases stress and blocks yielding in other zones. In contrast, failure around faults with smaller amplitude heights initiates at larger external loads, and therefore, more elastic energy is available for slip when failure occurs. Calculations of stress around fractal and nonfractal interfaces indicate that failure nucleation and locations are strongly dependent on the initial surface geometry. We suggest that stress asperities and barriers throughout the seismic cycle can be driven by the geometrical irregularities of the fault surface. Key Points: Off‐fault static stress pattern and failure conditions around rough interlocked fault surfaces are calculated using analytical solution Fault roughness heights and the amplitude to wavelength ratio shape the stress field and its magnitudes The multiscale geometry of preexisted fault surfaces determines the location and the threshold of nucleation zones along the fault